Spatio-temporal characterization of ultrashort vector pulses - Zdagkas, Apostolos (2022)
Ultrafast vectorially polarized pulses have found many applications in information and energy transfer owing mainly to the presence of strong longitudinal components and their space-polarization non-separability. Due to their broad spectra, such pulses often exhibit space-time couplings, which significantly affect the pulse propagation dynamics. Although such couplings usually result in reduced energy density at the focal spot, they have been utilized to demonstrate pulse shaping as in the case of a rotating or sliding wavefront as the pulse travels through its focal point. Here, we present a new method for the spatiotemporal characterization of ultrashort cylindrical vector pulses based on a combination of spatially resolved Fourier transform spectroscopy and Mach-Zehnder interferometry. The method provides access to spatially resolved spectral amplitudes and phases of all polarization components of the pulse. We demonstrate the capabilities of the method by completely characterizing a 10 fs radially polarized pulse from a Ti:sapphire laser centered at 800 nm.